Фітоіндикаційна оцінка динаміки режиму аерації техноземів Нікопольського марганцеворудного басейну - Маслікова, Катерина Павлівна; Maslikova, Kateryna (Національний університет біоресурсів і природокористування України, 2018)
In the work the regularities of the regime of technosols aeration dynamics in Nikopol manganese ore basin after agricultural reclamation were revealed. Experiments were conducted at the research station of Dnipro State Agro-Economic University (Pokrov, Dnipropetrovsk region, Ukraine). The temporal dynamics of phytoindication indexes changes was approximated by a Hill's equation. The analytical dependence between parameters of plant aeromorphes and soil porosity was proposed. It was shown that in the progress of the technosols soil forming process the increase of soil aeration regime is an important trend that in the vast majority of undermining the ecological conditions in them further from optimal for the vast majority of cultivated plants. In addition, this tendency makes the extreme conditions of existence for natural species of plants and pedobiont animals. У роботі встановлені закономірності динаміки режиму аерації техноземів Нікопольського марганцеворудного басейну протягом сільськогосподарської рекультивації порушених земель. Досліди проведені на науково-дослідному стаціонарі Дніпровського державного аграрноекономічного університету (м. Покров, Дніпропетровська область, Україна). Часова динаміка змін фітоіндикаційних показників була апроксимована рівнянням Хілла. Запропонована аналітична залежність між показниками рослинних аероморф та порозністю ґрунту. Показано, що у процесі ґрунтогенезу техноземів важливою тенденцією є збільшення показників режиму аерації ґрунтів, що віддаляє екологічні умови в них далі від оптимальних для переважної більшості культурних рослин.
Phytoindication assessment of the technosols aeration regime dynamics in Nikopol manganese ore basin
Keywords: повітряний режим ґрунту; air mode; аероморфи; aeromorphes; фітоіндикація; phytoindication; рекультивація; reclamation; часова динаміка; temporal dynamics; сукцесії; succession